Elegance and National Expression in Artistic Translation (Poetic and Prose) (Czech Journal of Multidisciplinary Innovations, 2023)
This article highlights and discusses the peculiarities of literary translation, the rules of law, the re-creation of national expressions in prose and prose translations and some shortcomings and successes through examples